Amulet. Book eight, Supernova - Kibuishi, Kazu, 1978- (Graphix, 2018)
When Emily loses control of her Amulet, she is imprisoned in the Void, where she must escape the influence of the Voice, while her brother, Navin, travels to a space station where the Resistance is preparing to battle the approaching Shadow forces.